Characterization of cold-tolerant trehalose-6-phosphate synthase from the deep-sea bacterium Microbacterium sediminis YLB-01. Issue 5 (3rd May 2020) - Tang, Xixiang; Yi, Zhiwei; Xu, Xiashutong; Xu, Rufang; Huang, Ping; Yu, Libo
ABSTRACT: A gene encoding the enzyme trehalose-6-phosphate synthase (TPS), which is part of the TPS trehalose synthesis pathway, was cloned from the deep-sea psychrotolerant bacterium Microbacterium sediminis YLB-01 and expressed in Escherichia coli BL21. The exogenously expressed TPS exhibited highest similarity (80.93% identity) to Microbacterium sp. TPS. The purified recombinant TPS was cold-tolerant, with low thermostability. The optimum temperature for TPS activity was 40°C, and the enzyme retained 72.6% of its maximal activity at 4°C. The optimum pH was 7.5. TPS activity was cation-dependent, with Mg 2+, Co 2+, or Ba 2+ being essential for maximum activity. The kinetic constants of the recombinant TPS reaction rates confirmed that it was cold-tolerant. Molecular dynamics analysis showed that TPS was more flexible (0.8741Å) at 4°C than 1GZ5, its homolog in the mesophilic bacterium E. coli, and superposition of the 3D enzyme structures supported this. Graphical Abstract: uf0001 Enzymatic properties of recombinant trehalose-6-phosphate synthase (TPS).